Comprehensive review of materials, applications, and future innovations in biodegradable esophageal stents - Yang, Yaochen; Yang, Yuanyuan; Hou, Zhipeng; Wang, Tingting; Wu, Peng; Shen, Lufan; Li, Peng; Zhang, Kai; Yang, Liqun; Sun, Siyu (Frontiers in Bioengineering and Biotechnology, 2023)
Esophageal stricture (ES) results from benign and malignant conditions, such as uncontrolled gastroesophageal reflux disease (GERD) and esophageal neoplasms. Upper gastrointestinal endoscopy is the preferred diagnostic approach for ES and its underlying causes. Stent insertion using an endoscope is a prevalent method for alleviating or treating ES. Nevertheless, the widely used self-expandable metal stents (SEMS) and self-expandable plastic stents (SEPS) can result in complications such as migration and restenosis. Furthermore, they necessitate secondary extraction in cases of benign esophageal stricture (BES), rendering them unsatisfactory for clinical requirements. Over the past three decades, significant attention has been devoted to biodegradable materials, including synthetic polyester polymers and magnesium-based alloys, owing to their exceptional biocompatibility and biodegradability while addressing the challenges associated with recurring procedures after BES resolves. Novel esophageal stents have been developed and are undergoing experimental and clinical trials. Drug-eluting stents (DES) with drug-loading and drug-releasing capabilities are currently a research focal point, offering more efficient and precise ES treatments. Emerging manufacturing technologies such as three-dimensional (3D) printing and new biodegradable materials such as hydrogels have also contributed to the innovation of esophageal stents. The ultimate objective of the research and development of these materials is their clinical application in the treatment of ES and other benign conditions and the palliative treatment of malignant esophageal stricture (MES). This review aimed to offer a comprehensive overview of current biodegradable esophageal stent materials and their applications, highlight current research limitations and innovations, and offer insights into future development priorities and directions.